Hypogonadism as a risk factor for cardiovascular mortality in men: a meta-analytic study - Corona, Giovanni; Rastrelli, Giulia; Monami, Matteo; Guay, André; Buvat, Jaques; Sforza, Alessandra; Forti, Gianni; Mannucci, Edoardo; Maggi, Mario (European journal of endocrinology, 2011)
ObjectiveTo verify whether hypogonadism represents a risk factor for cardiovascular (CV) morbidity and mortality and to verify whether testosterone replacement therapy (TRT) improves CV parameters in subjects with known CV diseases (CVDs).DesignMeta-analysis.MethodsAn extensive Medline search was performed using the following words ‘testosterone, CVD, and males’. The search was restricted to data from January 1, 1969, up to January 1, 2011.ResultsOf the 1178 retrieved articles, 70 were included in the study. Among cross-sectional studies, patients with CVD have significantly lower testosterone and higher 17-β estradiol (E2) levels. Conversely, no difference was observed for DHEAS. The association between low testosterone and high E2 levels with CVD was confirmed in a logistic regression model, after adjusting for age and body mass index (hazard ratio (HR)=0.763 (0.744–0.783) and HR=1.015 (1.014–1.017), respectively, for each increment of total testosterone and E2 levels; both P<0.0001). Longitudinal studies showed that baseline testosterone level was significantly lower among patients with incident overall- and CV-related mortality, in comparison with controls. Conversely, we did not observe any difference in the baseline testosterone and E2 levels between case and controls for incident CVD. Finally, TRT was positively associated with a significant increase in treadmill test duration and time to 1 mm ST segment depression.ConclusionsLower testosterone and higher E2 levels correlate with increased risk of CVD and CV mortality. TRT in hypogonadism moderates metabolic components associated with CV risk. Whether low testosterone is just an association with CV risk, or an actual cause–effect relationship, awaits further studies.